USO DE MODELO NÃO LINEAR PARA DESCREVER CRESCIMENTO DE TILÁPIAS DO NILO MELHORADAS GENETICAMENTE - Trindade, Tuanny; Dorce, Larissa; Nogueira, Sheila; Mendonca, Wesley Clovis; Azambuja, Junior Joaquim; Nunes, Angelina (ANAIS DO ENIC, 2018)
-